Mechanisms of influence of the microtubule over-stabilizing ligands on the structure and intrinsic dynamics of α, β-Tubulin. (February 2022) - Basu, Debadrita; Majumdar, Sarmistha; Mandal, Nishita; Dastidar, Shubhra Ghosh
Abstract: The intervention into the cell cycle progression by administering microtubule over-stabilizing ligands that arrest the mitotic cell division by preventing spindle dissociation, is a promising strategy to fight against cancers. The building blocks of the microtubules and the spindles, i.e. the α, β-tubulin dimer, upon binding of such ligands, stay more comfortably in the microtubular multimeric form; the phenomenon of which is the key to the said over-stabilization. Using two such over-stabilizing ligands, Taxol and Taxotere, the present work reports the collective changes that these ligands induce on the structure and dynamics of the α, β-tubulin dimer which could be reconciled as the molecular basis of the over-stabilization of the microtubules; the trends have been found to be statistically significant across all independent calculations on them. The ligand binding increases the coherence between the residue communities of the two opposite faces of the β-subunit, which in a periodic arrangement in microtubule are knwon to form intermolecular contact with each other. This is likely to create an indirect cooperativity between those structural regions and this is a consequence of the reshuffling of the internal network of interactions upon ligand binding. Such reorganizations are also complemented by the increased contributions of the softer modes of the intrinsic dynamics more, which is likely to increase the plasticity of the system favourable for making structural adjustments in a multimer. Further, the ligands are able to compensate the drawback of lacking one phosphate group in protein-GDP interactions compared to the same for protein-GTP and this is in agreement with the hints form the earlier reports. The findings form a mechanistic basis of the enhanced capacity of the α, β-tubulin dimer to get more favourably accommodated into the microtubule superstructure upon binding either of Taxol and Taxotere. Graphical Abstract: ga1 Highlights: The molecular mechanisms of the Taxol and Taxotere to influence the intrinsic dynamics of α, β-Tubulin dimer are revealed. The mechanisms could be correlated with the over-stabilize the α, β-Tubulin dimer in the microtubule. Taxol and Taxotere primarily reshuffles the internal network of interactions of the protein. It increases the cohesion between the remote sites, i.e. two regions of lateral contacts through internal network of interactions. The ultimate result is softening of the softer modes making the tubulin dimer more flexible and thus increasing the probability to fit it into the microtubule.